The relationship between transport, economic growth and environmental degradation for ninety countries - Listiono Listiono (Center for Science and Technology, IAIN Surakarta, 2018)
This paper examines the relationship between freight transport, economic growth, and environmental degradation (CO2 emissions) across ninety countries from 1980 to 2014. The analysis is divided into five groups: the global panel, high-income countries, upper-middle-income countries, lower-middle-income countries, and lower-income countries. This study employs a Simultaneous Equation Model, estimated using the Three-Stage Least Squares (3SLS) method. The results reveal a bi-directional causal relationship between economic growth and freight transport in both high-income and lower-income countries. Additionally, the findings indicate a bi-directional causality between transportation and CO2 emissions in upper-middle-income countries. Lastly, a bi-directional causality between economic growth and CO2 emissions is observed in lower-middle-income countries.